2019
DOI: 10.1002/ecs2.2642
|View full text |Cite
|
Sign up to set email alerts
|

Tidal regime influences the spatial variation in trait‐based responses of Suaeda salsa and edaphic conditions

Abstract: Tidal regime is recognized as a vital hydrological process in the restructuring of saltmarsh vegetation communities, resulting in differing edaphic conditions and ecosystem functions. Ample studies have focused on the context‐dependent effects of tidal disturbance on saltmarsh vegetation worldwide, particularly trait‐based responses to physical factors; however, to our knowledge, there are few insights into the edaphic conditions and responses of saltmarsh plants as well as plant–soil systems to tidal disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Metabolomics and proteomics have replaced other traditional molecular marker techniques and are often used as tools to determine the expression of vegetation characteristics ( Villate et al, 2021 ). Abiotic stress factors can directly affect the yield of plants and may cause apparent differences in plant characteristics, such as plant performance, growth, metabolism, and protein expression profiles ( Wu et al, 2012 ; Liu et al, 2015 ; Wang et al, 2019 , 2021 ). For example, in Ocimum basilicum L., the obvious effect of drought stress on phenylpropanoid biosynthesis increases the content of methyl tea phenol and methyl eugenol and then alters the expression profiles of leaves ( Mandoulakani et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics and proteomics have replaced other traditional molecular marker techniques and are often used as tools to determine the expression of vegetation characteristics ( Villate et al, 2021 ). Abiotic stress factors can directly affect the yield of plants and may cause apparent differences in plant characteristics, such as plant performance, growth, metabolism, and protein expression profiles ( Wu et al, 2012 ; Liu et al, 2015 ; Wang et al, 2019 , 2021 ). For example, in Ocimum basilicum L., the obvious effect of drought stress on phenylpropanoid biosynthesis increases the content of methyl tea phenol and methyl eugenol and then alters the expression profiles of leaves ( Mandoulakani et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the S. salsa in the degraded coastal salt marshes was restored initially, but the plant biomass was still lower than at the SS reference wetlands (Figure 2). This might be due to the complex environment of the coastal salt marshes (Wang et al, 2019), and although PA and BC additions improved the soil physicochemical properties, the effects of hydrological and topographical conditions on S. salsa were not considered in this study. In addition, the sample collection time was only 21 months from the time of carbon‐rich additive application, which was not long enough for complete restoration, with less plant litter input and decomposition (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Generally, the S. salsa in the degraded coastal salt marshes was restored initially, but the plant biomass was still lower than at the SS reference wetlands (Figure 2). This might be due to the complex environment of the coastal salt marshes (Wang et al, 2019), and although PA and BC additions improved the soil physicochemical properties, the effects of hydrological and topographical conditions on S. salsa…”
Section: Effects Of In Situ Applications Of Reed Straw and Biochar On...mentioning
confidence: 99%
“…The environment of the estuarine system is affected by the interaction of the sea and land (Wang et al, 2019). Previous studies have shown that physicochemical factors regulate the community diversity, structure and function of microorganisms (Ren et al, 2019;Sun et al, 2020).…”
Section: Impacts Of Physicochemical Factors On Estuarine Bacteriamentioning
confidence: 99%